Correlation of Proinflammatory and Anti-Inflammatory Cytokine Levels with Histopathological Changes in an Adult Mouse Lung Model of Campylobacter jejuni Infection - Al-Banna, Nadia (American Society for Microbiology (ASM), 2008)
Campylobacter jejuni is a major cause of diarrhea in humans. A mouse lung model of infection was previously established for C. jejuni. We used this model to study cytokine production in the lungs and correlated it with pathological changes. C. jejuni strain 81-176 or sterile phosphate-buffered saline was intranasally inoculated into adult BALB/c mice. The levels of proinflammatory cytokines (gamma interferon, tumor necrosis factor alpha, interleukin-1β [IL-1β], IL-2) and anti-inflammatory cytokines (IL-4, IL-10), in addition to those of IL-6, were assessed on days 1, 3, and 5 postinfection by enzyme-linked immunosorbent assay, and the ratios of proinflammatory cytokines to anti-inflammatory cytokines were calculated. Since IL-6 is unique in that it is both a proinflammatory cytokine and a TH2 cytokine, it was considered to be both in the determination of these ratios. The significance of the cytokine levels and ratios were determined by the Mann-Whitney U test (P ≤ 0.05). The induction of proinflammatory cytokines in the lungs of infected mice, as indicated by the cytokine levels and ratios, coincided with the accumulation of neutrophils and activated macrophages, in addition to the clearance of the bacterial load and bacteriumlike structures that we have previously shown in the same groups of mice. This was followed by increased levels of anti-inflammatory cytokines and the resolution of inflammation and pathology in the lungs. This study demonstrates the dynamics of cytokine production and their correlation with tissue inflammation and the resolution of infection. This model is useful for further studies of the pathogenesis of C. jejuni infection and vaccine evaluation.